Agroecological Management of the Grey Mould Fungus Botrytis cinerea by Plant Growth-Promoting Bacteria - Ma. del Carmen Orozco-Mosqueda; Ajay Kumar; Ayomide Emmanuel Fadiji; Olubukola Oluranti Babalola; Gerardo Puopolo; Gustavo Santoyo (Plants, 2023)
Botrytis cinerea is the causal agent of grey mould and one of the most important plant pathogens in the world because of the damage it causes to fruits and vegetables. Although the application of botrycides is one of the most common plant protection strategies used in the world, the application of plant-beneficial bacteria might replace botrycides facilitating agroecological production practices. Based on this, we reviewed the different stages of B. cinerea infection in plants and the biocontrol mechanisms exerted by plant-beneficial bacteria, including the well-known plant growth-promoting bacteria (PGPB). Some PGPB mechanisms to control grey mould disease include antibiosis, space occupation, nutrient uptake, ethylene modulation, and the induction of plant defence mechanisms. In addition, recent studies on the action of anti-Botrytis compounds produced by PGPB and how they damage the conidial and mycelial structures of the pathogen are reviewed. Likewise, the advantages of individual inoculations of PGPB versus those that require the joint action of antagonist agents (microbial consortia) are discussed. Finally, it should be emphasised that PGPB are an excellent option to prevent grey mould in different crops and their use should be expanded for environmentally friendly agricultural practices.